Reporting on labour - Costain, Gene (Javnost (Ljubljana), 2005)
One of the central questions in this study was whether a group of mainstream labour reporters could create a culture of resistance in their journalism practice. This research also tested a dual conception of the group as an interpretive community and a culture of dissent, rather than as just members of a profession adhering to the rigidities of their professional roles in the mainstream press. The goal in this study was to shed light on the reporters' unique roles during a specific period of change, and to view them as interpreters of unfolding social events during a time of significant political change.
Keywords: Canada; Kanada; delavci; razredna zavest; politične spremembe; družbene spremembe; novinarji; novinarstvo; journalism; poročanje; obveščanje; objektivnost